LITERATURE ANALYSIS OF PHYLOTAXIS PATTERN VARIATION IN PLANTS: SYMMETRY, CLASSIFICATION, AND SPECIES REPRESENTATION - Khairy, R. Naufal (Bio-Lectura : Jurnal Pendidikan Biologi, 2025)
Phyllotaxis, or the pattern of leaf arrangement along a plant stem, plays a crucial role in physiological efficiency and morphological adaptation. This study aims to examine the variation in phyllotactic patterns among plants, identify their relationship with morphological symmetry, and provide examples of species that exhibit each pattern. Through a systematic literature review method, various relevant scientific sources on phyllotaxis and leaf morphological symmetry were analyzed, including journals, textbooks, and previous review articles. The analysis revealed two main categories of phyllotaxis: alternate and whorled. In alternate phyllotaxis, patterns such as distichous, spiral, semidecussate, and orixate arrangements were identified, whereas whorled phyllotaxis included decussate, tricussate, and tetracussate patterns. Each pattern exhibits distinct symmetry characteristics, including reflection, rotational, and spiral symmetries. The study also found that variations in phyllotactic patterns demonstrate profound geometric regularities, which are associated with plant adaptive strategies for light capture and internal resource distribution. This review provides new insights into the understanding of phyllotaxis in the context of morphological geometry and the distribution of plant species exhibiting each pattern.